Upaya Peningkatan Status Gizi Anak sebagai Pencegahan Stunting di Desa Mongiilo Utara Bone Bolango - Fika Nuzul Ramadhani; Endah Nurrohwinta Djuwarno; Nur Ayun R Yusuf (Jurnal Pengabdian Masyarakat Farmasi : Pharmacare Society, 2022)
Nutritional problem is one of the causes of increasing stunting incidence in an area which has a long term impact for children. Stunting in children is characterized by a child's height that is below average or also known as failure to thrive. Stunting in children can cause developmental delays in the brain so that long-term effects can cause mental retardation, low learning ability and the risk of chronic disease. Innovation in food sector by making biscuits with nuts and vegetable composition is very important to increase children's interest for consuming vegetables that are rich in nutrients for prevent stunting. This community service activity aims to prevent stunting in the people of North Mongiilo Village by providing information processing of biscuits with many nutrient. This service is carried out by providing information through video tutorials on making biscuits and explaining directly to the public about the benefits and nutritional content of the ingredients used in making biscuits. Providing information on how to make biscuits to the community received a good response because most people did not know about innovations in making biscuits made from nuts and vegetables that children could like. This service provides great benefits for the village community in order to gain knowledge about the benefits and important nutritional content of vegetables and improve the community's economy with innovations in production of biscuits made from nuts and vegetables.